Pendidikan Karakter Anak melalui Hadis tentang Kasih Sayang dan Kepedulian - Lita Yuniarti (Pendekar: Jurnal Pendidikan Berkarakter, 2025)
Abstract: Character education is one of the essential aspects in shaping a child’s personality. In Islam, the values of compassion and empathy hold a central position as moral foundations taught through hadith. This study aims to examine the role of hadiths related to compassion and empathy in shaping children’s character. The research method used is library research with a descriptive-analytical approach to hadith texts and their relevance to character education. The research instruments consist of documents and primary literature sources, namely hadith collections such as Sahih Bukhari and Sahih Muslim, as well as secondary sources including books and scholarly articles discussing character education and Islamic moral values. The data analysis technique involves several stages: data reduction, classification of hadiths based on the themes of compassion and empathy, interpretation of the contextual meanings of the hadiths, and drawing conclusions regarding their implications for character development in children. The results of the study show that hadiths emphasizing compassion-such as the encouragement to be gentle and caring toward others-provide a strong ethical foundation for instilling noble values in children. By integrating these values into education, children not only grow into morally upright individuals but also become capable of contributing positively to society. This study affirms the importance of applying hadith-based values in character education as an effort to build a generation with Islamic personality and integrity.Abstrak: Pendidikan karakter merupakan salah satu aspek penting dalam pembentukan kepribadian anak. Dalam Islam, nilai-nilai kasih sayang dan kepedulian menempati posisi sentral sebagai fondasi moral yang diajarkan melalui hadis. Penelitian ini bertujuan untuk mengkaji peran hadis yang berkaitan dengan kasih sayang dan kepedulian dalam membentuk karakter anak. Metode penelitian yang digunakan adalah kajian literatur (library research) dengan pendekatan deskriptif-analitis terhadap teks-teks hadis serta relevansinya dengan pendidikan karakter. Instrumen penelitian berupa dokumen dan sumber literatur primer, yaitu kitab-kitab hadis seperti Sahih Bukhari, Sahih Muslim, dan sumber sekunder berupa buku serta artikel ilmiah yang membahas pendidikan karakter dan nilai-nilai moral Islam. Teknik analisis data dilakukan melalui tahapan reduksi data, klasifikasi hadis berdasarkan tema kasih sayang dan kepedulian, interpretasi makna kontekstual hadis, serta penarikan kesimpulan mengenai implikasinya terhadap pembentukan karakter anak. Hasil penelitian menunjukkan bahwa hadis-hadis tentang kasih sayang, seperti anjuran untuk bersikap lemah lembut dan peduli terhadap sesama, memberikan landasan etis yang kuat untuk menanamkan nilai-nilai luhur pada anak. Dengan mengintegrasikan nilai-nilai ini ke dalam pendidikan, anak tidak hanya tumbuh menjadi individu yang berakhlak mulia, tetapi juga mampu berkontribusi positif dalam masyarakat. Penelitian ini menegaskan pentingnya penerapan nilai-nilai hadis dalam pendidikan karakter sebagai upaya membangun generasi yang berkepribadian Islami dan berintegritas.